Mycotoxins: risks to human health due to daily ingestion of contaminated food and its occurrence in clinical samples (Research, Society and Development, 2020)
Toxigenic fungi can produce mycotoxins in food in favorable conditions of temperature and humidity. The daily intake of mycotoxins in food can cause harm to human and animal health. The aim of this study was to verify the exposure of the human organism to mycotoxins and their occurrence in clinical samples. The current study evaluated the risks to human health due to the toxicity caused by mycotoxins when consumed daily in foods, as well as their occurrence in clinical samples. In this bibliographic revision, the articles were selected through a database using combined words to search of main subject, which were recruited 60 papers for the general revision and 20 papers for the data of exposure mycotoxins by the daily intake and mycotoxins in clinical samples. Mycotoxins are often found in foods, including cereals, pulses, fruits and vegetables. They are highly resistant molecules that remain even after processing in the industry, including their by-products. Chronic intoxication can occur in individuals, causing health damage. The mycotoxins found in clinical samples of individuals from a region can help in the knowledge of how much the population is exposed. Thereby, it is possible take preventive measures in order to avoid possible diseases. The mycotoxins exposure has essential importance to public health, once that it may assist in the prevention or reduction of diseases. This review may contribute to instigate new research on the possible relation between mycotoxin exposure and the diseases caused by its interaction with the organism.